ผู้ป่วยหลอดเลือดดำส่วนลึกที่ขาอุดตันในโรงพยาบาลสวรรค์ประชารักษ์ : Deep Vein Thrombosis in Sawanpracharak Hospital - Chotiwarangkul, Worawit (Region 3 Medical and Public Health Journal - วารสารวิชาการแพทย์และสาธารณสุข เขตสุขภาพที่ 3, 2018)
วัตถุประสงค์ : เพื่อศึกษาลักษณะทั่วไป ลักษณะทางคลินิก อัตราการเสียชีวิต และปัจจัยที่เกี่ยวข้องของผู้ป่วยหลอดเลือดดำส่วนลึกที่ขาอุดตัน (Deep vein thrombosis : DVT) สถานที่ศึกษา : โรงพยาบาลสวรรค์ประชารักษ์ รูปแบบการวิจัย : การศึกษาเชิงพรรณนาแบบย้อนหลัง กลุ่มตัวอย่าง : ผู้ป่วยทุกคนที่ได้รับการวินิจฉัย DVT อายุ 15 ปีขึ้นไป มีผลการรักษาและติดตามอย่างน้อย 6 เดือนและมีข้อมูลในเวชระเบียนในปี 2559 จำนวน 81 คน วิธีการศึกษา : รวบรวมข้อมูลจากเวชระเบียนด้านลักษณะบุคคล ลักษณะทางคลินิก และการเสียชีวิตเปรียบเทียบความแตกต่างด้านเพศและปัจจัยที่เกี่ยวข้องด้วยการทดสอบ Chi-Squareและ Student’s t-test กำหนดระดับนัยสำคัญทางสถิติที่ P น้อยกว่า 0.05 ผลการศึกษา : ผู้ป่วยอายุเฉลี่ย 62.3 ± 13.8 ปี เพศหญิงร้อยละ 60.5 ค่าดัชนีมวลกายเฉลี่ย 25.1 ± 5.7 กิโลกรัมต่อตารางเมตร ระยะเวลานอนโรงพยาบาลมีค่ามัธยฐาน 8 วัน ต่ำสุด 1 วัน สูงสุด 66 วัน ไม่พบความแตกต่างของจำนวนผู้ป่วยหญิงและชาย และไม่พบความแตกต่างระหว่างเพศกับอายุ ดัชนีมวลกาย ปัจจัยเกี่ยวข้องโรคมะเร็ง โรคร่วมกลุ่มเสี่ยง atherosclerosis และการเสียชีวิตของผู้ป่วยเพศหญิงพบการอุดตันที่ขาซ้าย ร้อยละ 75.5 สูงกว่าเพศชายอย่างมีนัยสำคัญทางสถิติ (p=0.005) ส่วนใหญ่มีการอุดตันของ หลอดเลือดดำที่ femoral veins มีปัจจัยที่เกี่ยวข้องโรคมะเร็ง ร้อยละ 56.8 มีภาวะติดเตียง ร้อยละ 19.8 และไม่ทราบสาเหตุร้อยละ 21.0 เพศชายพบมะเร็งต่อมลูกหมาก ร้อยละ 38.9 เพศหญิงพบมะเร็งทางนรีเวช ร้อยละ 53.6 มีภาวะแทรกซ้อน pulmonary embolism ร้อยละ 9.9 post thrombotic syndrome ร้อยละ 4.9 อัตราการเกิดซ้ำ ร้อยละ 6.2 มีเลือดออกรุนแรงหลังได้รับยาป้องกันการแข็งตัวของเลือดร้อยละ 12.3 ผู้ป่วยกลุ่มไม่ทราบสาเหตุหลัง 6 เดือนพบเป็นมะเร็ง ร้อยละ 11.8 พบอัตราการเสียชีวิต ร้อยละ 22.2 วิจารณ์และสรุป : ผู้ป่วยหลอดเลือดดำส่วนลึกที่ขาอุดตันพบมากในกลุ่มอายุ 60 ปีขึ้นไปเพศหญิงพบมากกว่าและพบการอุดตันที่ขาซ้ายสูงกว่าเพศชายผู้ป่วยส่วนใหญ่มีปัจจัยเกี่ยวข้องโรคมะเร็งมากที่สุดดังนั้นควรค้นหามะเร็งต่อมลูกหมากในผู้ป่วยชายและมะเร็งทาง นรีเวชในผู้ป่วยหญิงเนื่องจากพบมาก และเฝ้าระวังภาวะเลือดออกรุนแรงหลังการได้ยา anticoagulant โดยเฉพาะในผู้ป่วยกลุ่มเสี่ยง การวินิจฉัยและรักษาผู้ป่วย VTE ที่ถูกต้องรวดเร็วจะลดอัตราตายได้มาก ควรมีการศึกษาข้อมูลที่ขนาดใหญ่ขึ้นและมีการติดตามผู้ป่วยระยะเวลามากขึ้นอย่างเหมาะสมต่อไป คำสำคัญ : หลอดเลือดดำส่วนลึกที่ขาอุดตัน,โรงพยาบาลสวรรค์ประชารักษ์ Abstract Objective : To study individual and clinical characteristics, patient dead rate and factors associated with deep vein thrombosis : DVT patients. Setting : Sawanpracharak Hospital Design : Retrospective study methods Subjects : 81 patients who were beyond 15 years old with diagnosed DVT and follow up for 6 months or more those who admitted during January 2016 – December 2016 Methods : Data corrected from medical records. To study individual and clinical characteristic, patient dead rate and compare the difference of factors associated with DVT patients by using Student’s t test and Chi-Square test (P =< 0.05) Results : The average age was 62.3 ± 13.8 years. Females were 60.5%, the median length day in hospital was 8.0 days, the average body mass index (BMI)= 25.1 ± 5.7, there were not statistically significant correlation between males and females, sexes and average age, average BMI, malignancy, atherosclerosis risk and mortality rate of patients. However, more DVT patients in females, lower average age in females, high average of BMI, malignancy, atherosclerosis risk than males. The mortality rate of males higher than females. The affected vein in lower extremity of females were found in left leg 75.5% with statistically significant correlation between male and female (p=0.005). More common affected vein in patients was femoral vein. DVT was associated with malignancy in DVT patients 56.8%, bed ridden 19.8% and idiopathic 21.0%. Common in malignancy of prostate was 38.9% in males and gynecological malignancy was 53.6% in females. Pulmonary embolism were occurred 9.9%, post thrombotic syndrome was found 4.9% and recurrent DVT was found 6.2% in DVT patients. Major bleeding in patients after treatment of anticoagulant was occurred 12.3%. Malignancy occurred during follow-up at least 6 months 11.8%. The mortality rate of patients 22.2%, males were high mortality rate than females, but not statistically significant mortality rate of them. Conclusion : DVT patients in this study more common found in 60 years of age and over, more common in females, the affected vein occlusion in lower extremity of females were found high rate in left leg, with statistically significant correlation between male and female (p=0.005). Femoral veins were found commonly occlusion in DVT patients. High average BMI, malignancy and atherosclerosis risk in female. Malignancy was the most common associated factor of patients. Most common malignancy of prostate found in males and gynecological malignancy in females. Pulmonary embolism and major bleeding in patients after treatment of anticoagulant was high rate than other study. The mortality rate was high in males. Therefore, should be investigate malignancy of prostate in males and gynecological malignancy in females of DVT patients. To monitor major bleeding in patients after treatment of anticoagulant. Rapidly diagnostic and treatment have been reduced mortality rate. Further study is required in greater DVT patients group and longer term follow up for more property management and efficiency in the future. Keywords : Deep vein thrombosis, Sawanpracharak Hospital